Experimental and Density Functional Theory Characteristics of Ibrutinib, a Bruton’s Kinase Inhibitor Approved for Leukemia Treatment - Ismail, Ali I. (Journal of Spectroscopy, 2021)
Ibrutinib, a Bruton’s tyrosine kinase that plays an essential role in the B-cell development and cancer cells, has been recently approved to treat chronic, lymphocytic, and other types of leukemia. This study focused on investigating ibrutinib by its electronic transitions, vibrational frequencies, and electrospray mass spectra. The experimental peaks for electronic spectrum were found at 248.0 and 281.0 nm, whereas the νC = 0 stretching frequency was found at 1652.4 and 1639.19 cm−1. These experimental properties were compared with the corresponding theoretical calculations in which density functional theory was applied. The optimized structure was obtained with the calculations using a hybrid function (B3LYP) and high-level basis sets [6-311G++(d,p)]. Most of the calculated vibrational frequencies showed a relatively good agreement with the experimental ones. The electronic transitions of ibrutinib calculated using time-dependent DFT method were performed at two different solvation methods: PCM and SMD. The mass spectrum of ibrutinib, its fragments, and its isotopic pattern agreed well with the expected spectra.